Nilai Pendidikan Religius dalam Musik Rofa Band di Pondok Pesantren Raudlatul Fatihah Pleret Bantul Yogyakarta - Isnaini Nur ‘Ainun; Ali Mustaqim; Ahmad Shofiyuddin Ichsan (Berkala Ilmiah Pendidikan, 2022)
This research aimed to reveal the values ​​of religious education in the art of music Rofa Band at religious Boarding School Raudlatul Fatihah Pleret Bantul Yogyakarta. This research was a field research with descriptive qualitative method and using a case study approach. The data collection used observation, interviews, and documentation. While the data analysis method used Seiddel analysis. The results of this study could be understood that the Rofa Band musical art performance at this Islamic boarding school had two activities, namely music performances and routine whiz with musicians. The da'wah method carried out by Kyai in inserting the value of Islamic education in each of his activities was through three methods, namely lectures, question and answer, and proverbs. The impact of the implementation of Rofa Band music was as an expression of love and beauty, as an exaltation of the Creator, the birth of good relations (between humans and God and fellow humans), the realization of good relations between aqidah, sharia and morals, and making everything before bad for the better.